O travestismo narrativo em O Professor, de Charlotte Brontë - Rodrigues, Sara Novaes (2016)
In The Professor, the first novel she tried to publish, Charlotte Brontë, English writer who lived in the 19th century, makes use of a literary technique called narrative transvestism, which is characterized by the use of an autodiegetic narrator of the opposite sex. With the objective of analysing the novel, I present the author’s biography, as well as the critiques she and her book have received since its publication. After that, I bring a study about narrative, as a preparation to present the several different denominations and use of the narrative transvestism. In addition, I analyse the way the author uses the technique in the novel. In the last chapter, I present my own reading of certain parts of the novel, with the aid of specialized studies about the author and the novel.